(untitled) (Global Journal of Management and Business Research, 2019)
In this paper, we attempt to study the influence of institutional quality on the attractiveness of foreign direct investment (FDI) with a sample of MENA countries during a study period from 1996 to 2015. For this purpose, we will synthesize different empirical researches that have described direct and indirect correlation between governance and FDI. Thus, we will collect a database from the World Bank and the International Monetary Fund on macroeconomic variables, institutional variables and FDI on national wealth. We will use the Static Panel technique to identify the governance effect on FDI for the MENA region.